"A Bridge Between High School and College": A Case Study of a STEM Intervention Program Enhancing College Readiness Among Underserved Students. (May 2020) - Lane, Tonisha B.; Morgan, Kali; Lopez, Megan M.
Underserved students express a high interest in earning a science, technology, engineering, and mathematics (STEM) degree. However, their ACT benchmark indicators tend to be much lower than their peers, especially for students who report more than one underserved attribute. There are a number of STEM intervention programs (SIPs) that are designed to retain and graduate underserved students in STEM. Yet, relatively few engage in theoretically driven, empirical research to elucidate what program components contribute to college readiness. Using Conley's college and career readiness framework, this qualitative case study examined how one SIP helped underserved students overcome academic barriers and acquire context-specific knowledge. Findings revealed that nine interrelated practices and activities contributed to students feeling better prepared for the STEM curriculum and college expectations. Still, more attention could have been devoted to advancing key cognitive strategies. This article concludes with practical implications for SIP program administrators and faculty.